Teacher-Student Relations in Children with Speech Delays: Relasi Guru Siswa Pada Anak Terlambat Bicara - Rokayani, Rika Badriyatur; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe the forms of teacher-student relationships in children with speech delays. The method used in this research is a qualitative case study method using two research subjects, namely people who work teacher with special needs students who are experienced in assisting and educating children with special needs. The characteristics of the accompanying teacher in this study are the teachers who accompanied children with speech delays, female, experienced in assisting children with speech delays, have a special educational background, have attended training on special education, have competence in dealing with children with specia needsl, have a high sense of empathy. The subject in this study using the purposive sampling technique. The data collection method used interviews. The results of the study indicate that teacher student relationship have unique characteristics. It happens on three aspects, which are conflict, closeness, and dependence. A good student-teacher relationship occurs when the teacher is caring, has more attention, patiently accompanies, and wants to give the best for late-talking children. The impact of the teacher's relationship with children who encounter speech delays is that the child feels comfortable with the accompanying teacher and becomes more diligent in studying. So, as the teacher with special needs students have good relationships with children with speech delays, they feel more grateful, empathize and care for children with special needs. It also happens reciprocally.